Digitalne inventarne knjige entomoloških študijskih zbirk in podatkovna zbirka fotografij nevretenčarjev iz Prirodoslovnega muzeja Slovenije - Trilar, Tomi (Knjižnica, 2012)
In the age of information technology it is one of the primary activities of museums to digitise the national cultural heritage, or, as in the case of the Slovenian Museum of Natural History, to digitise the natural cultural heritage. In addition to Digital Inventory books we present Visual Inventory Books and Database of Invertebrate Pictures which serve as a source of metadata for public access to the internet and providing information to the international professional community.
Keywords: cultural heritage; kulturna dediščina; naravoslovje; nevretenčarji; dokumentiranje; digitalizacija; digitization; muzeji; muzejske zbirke; Prirodoslovni muzej Slovenije; Slovenian Museum of Natural History